THE ROLE OF BIBLIOMETRIC ANALYSIS OF ARTIFICIAL INTELLIGENCE (AI) IN ACCOUNTING: A STUDY FROM SCIENCEDIRECT, EMERALD INSIGHT, AND SCOPUS DATABASES - Taufiqurrahman, Muhammad; Lating, Ade Irma Suryani (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine publication trends related to AI in accounting using a bibliometric approach, by identifying influential authors, key keywords, and patterns of scientific collaboration. Method: Research data was taken from 50 publications on the Scopus, ScienceDirect, and Emerald Insight databases between 2021 and 2025, and then analyzed using VOSviewer 1.6.20 software with co-authorship and co-occurrence techniques. Results: The analysis results confirm that